Determination of Heavy Metal Levels in Some Weeds Collected from Tokat, Turkey - Kadioglu, Izzet; Mendil, Durali; Sari, Hayati; Hasdemir, Erdogan (Asian Journal of Chemistry, 2016)
Eleven species of weed samples were collected from Tokat in Turkey, which negatively affect germination of crop plants were analyzed for heavy metals by AAS. Six trace metals (Fe, Mn, Cu, Ni, Zn and Cr) in the samples were determined using flame and graphite furnace atomic absorption spectrometry after microwave digestion. The metal concentrations in samples were found to be 122-695, 13.9-96.5, 4.3-17.3, 1.9-8.5, 13.1-30.3 and 1.0-5.5 μg/g for iron, manganese, copper, nickel, zinc and chromium respectively. The high metal accumulation levels in the species were found in Hypericum perforatum L. for Fe, Cr, Sorghum halepense (L.) Pers for Mn, Solanum nigrum L. for Cu, Zn and Consolida regalis SF Gray for Ni.